Performance of a Magnetic Fluid Based Squeeze Film Between Transversely Rough Triangular Plates - R. M. Patel; G. M. Deheri; P. A. Vadher (Tribology in Industry, 2010)
Efforts have been made to study and analyze the effect of transverse surface roughness on the performance of a magnetic fluid based squeeze film between triangular plates. The roughness of the bearing surfaces is characterized by a stochastic random variable with non-zero mean variance and skewness. The associated Reynolds’ equation is stochastically averaged with respect to the random roughness parameter in turn, which is solved with appropriate boundary conditions to obtain the pressure distribution. From this, the expression for load carrying capacity is derived. The results suggest that the magnetization parameter increases the load carrying capacity while the load carrying capacity gets decreased due to the standard deviation. It is seen that the negatively skewed roughness increases the load carrying capacity substantially especially, when the negative variance is involved. It is revealed that the negative effect induced by the standard deviation can be minimized by the positive effect of the magnetization parameter in the case of negatively skewed roughness.